2022
DOI: 10.1093/scan/nsac016
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances basolateral amygdala activation and functional connectivity while processing emotional faces: preliminary findings in autistic vs non-autistic women

Abstract: Oxytocin is hypothesized to promote social interactions by enhancing the salience of social stimuli. While previous neuroimaging studies have reported that oxytocin enhances amygdala activation to face stimuli in autistic men, effects in autistic women remain unclear. In this study, the influence of intranasal oxytocin on activation and functional connectivity of the basolateral amygdala – the brain’s “salience detector” – while processing emotional faces vs. shapes was tested in 16 autistic and 21 non-autisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Our major-and to our knowledge, novel-finding was the presence of widespread interaction effects across all local graph metrics and across a multitude of brain regions, suggesting that oxytocin modulates network properties in a clinical status-specific manner. This is consistent with the differential effects of oxytocin on timeseries correlational connectivity reported in a variety of clinical populations vs healthy controls, including patients with social anxiety (47,76), post-traumatic stress disorder (48), and autism (49). Here we demonstrate, for the first time, that this is also the case in terms of effects on functional brain network topology in people at CHR-P.…”
Section: Group X Treatment Interaction Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…Our major-and to our knowledge, novel-finding was the presence of widespread interaction effects across all local graph metrics and across a multitude of brain regions, suggesting that oxytocin modulates network properties in a clinical status-specific manner. This is consistent with the differential effects of oxytocin on timeseries correlational connectivity reported in a variety of clinical populations vs healthy controls, including patients with social anxiety (47,76), post-traumatic stress disorder (48), and autism (49). Here we demonstrate, for the first time, that this is also the case in terms of effects on functional brain network topology in people at CHR-P.…”
Section: Group X Treatment Interaction Effectssupporting
confidence: 88%
“…In our previous CHR-P work, we demonstrated that oxytocin modulates frontal activation during mentalising (42), anterior cingulate neurochemistry (43) and resting cerebral blood flow in the hippocampus among numerous other regions (44). Independent evidence further suggests that oxytocin modulates connectivity within resting-state networks in healthy volunteers (45,46) and ‘normalises’ aberrant connectivity in several clinical populations, including patients with social anxiety (47), post-traumatic stress disorder (48) and autism (49). Moreover, a recent study in healthy males demonstrated that a single dose of oxytocin was sufficient to modulate local functional network topology, including in regions and networks implicated in the pathophysiology of psychosis (50).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigating 16 autistic and 21 non-autistic women showed pronounced differences in the functional connectivity of the amygdala to various other brain areas between the two groups [ 37 ]. Thus, we calculated a psychophysiological interaction (PPI; [ 18 ]) with the bilateral amygdala as seed region.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the amygdala theory of autism [ 5 ], which assumes amygdala alterations to be (partly) responsible for differences between autistic and non-autistic individuals, several studies showed significantly decreased amygdala activation in autistic individuals when presented with emotional stimuli in functional magnetic resonance imaging (fMRI) [ 4 , 20 ]. Other studies, however, have found increased amygdala activation [ 28 , 36 , 45 ] and yet others have shown no difference at all [ 21 ] or no difference in local activation, but differences in functional connectivity [ 37 ]. A recent meta-analysis on face processing in autism (including several tasks using emotional stimuli) found a lower activation of the amygdala during face processing to be the only statistically significant alteration in autistic participants [ 10 ]; the authors, however, used two different statistical ways to compute the meta-analysis and found significant results in the amygdala only with one of them.…”
Section: Introductionmentioning
confidence: 99%
“…OT has been found to reduce amygdala activation to negative emotional stimuli in healthy males [ 24 , 26 , 38 ] and particularly in those participants with enhanced reactivity to social threat such as patients with affective or anxiety-related disorders [ 29 , 61 63 ]. By contrast, OT has been reported to increase amygdala activation in participants with lower amygdala activation to emotional faces such as patients with autistic spectrum disorder [ 64 , 65 ]. Whereas the findings of OT effects on anger-related amygdala activation is consistent to the literature, we report that increased amygdala activation under OT in response to fearful stimuli in healthy controls is surprising and in contrast with previous studies in healthy men [ 24 , 66 ].…”
Section: Discussionmentioning
confidence: 99%